Effects of pure and impure carbon dioxide (CO2) on soil chemistry - Wei, Yang (2013)
A cleaner use of fossil fuels supported by Carbon Capture and Storage (CCS) techniques is considered to be one of the main short-term strategies for addressing the global climate change problem. However, potential CO2 or CO2/SO2 seepage during some of the phases of a CCS project not only reduces its performing efficiency, but also impacts the local environment, which could have further impacts on human health. It is therefore essential to assess the potential risks and provide evidence that the impacts are well understood. Moreover, studying the effects of CO2 leakage is useful for identifying monitoring parameters if the leakage does happen, leading to the development of new approaches in detecting CO2 leaks. Accordingly, this research is carried out to assess the relevant impacts on the local environment of CO2 leakage, focusing on the environmental impacts caused by CO2 seepage associated with various soil types, mostly on the soil geochemical changes, which is currently lacked.